To begin you must identify the co-efficients of each x term, essentially what number comes before x^{2 }, x and the integer value.

a = 1, b = 3, c = -4 . We then substitute these values into the quadratic formula: x = ( -b +- SQRT (b^{2} - 4ac) ) ÷ 2a . For the top half of the formula we end up with: - 3 +- SQRT (3^{2 }- 4 x 1 x (-4)). This simplifies to -3 +- 5 = 2 or -8.

On the bottom of the formula we simply get 2 x 1 = 2. Therefore our 2 answers for x are x = 2 ÷ 2 or x = -8 ÷ 2 which results in x being equal to x = 1 or -4.